Autoclaving of alkali-activated materials. (November 2019) - Mierzwiński, D; Walter, J
Abstract: Alkali-activated materials are amorphous materials that look like natural stone or a concrete structure. As in the case of concrete, on the surface of alkali-activated materials, a white coating appears in the form of efflorescence. For conventional efflorescent concrete, the reaction between Ca(OH)2 with water and CO2 is generally harmless, except for the discolouration. In the case of alkali-activated materials, efflorescence can be a big problem, especially if they are exposed to moisture or in contact with water. The white efflorescence on the surface of the materials is sodium carbonate heptahydrate Na2 CO3 ·7H2 O [1]. Various chemicals to prevent primary and secondary efflorescence can be used to reduce the appearance of the efflorescence. In the case of alkali-activated materials, this is a more complex process. The following paper proposes the use of hydrothermal processing during alkali-activated materials production. Hydrothermal treatment in an autoclave significantly reduced the appearance of efflorescence on the alkali-activated materials surfaces.